The Effect of Intervention Based on Pender's Model of Health-Promoting Self-Care Behaviors in Women who are the Head of their Household - Khosravan; Alami; Mansoorian; Kamali (Kashan University of Medical Sciences, 2016)
Background A number of studies have reported that women as the head of the household suffer from poor physical health. Yet, a few studies are available on the effects of health-promoting interventions for this vulnerable group. Objectives The present study was conducted to determine the effect of an intervention based on Pender's model on health-promoting behaviors in women who were the head of their household. Methods A quasi-experimental study was conducted on 66 women, who were the heads of households with inappropriate physical health-promoting behaviors, selected by the consensus method and allocated to intervention and control groups using the randomized permuted block method. The intervention group received supportive-educational intervention according to Pender's model. Posttest was carried out for both intervention and control groups two months after the end of the intervention. Data were analyzed using descriptive statistics and inferential tests, including independent samples t, paired t, Chi-square, Mantel-Haenszel tests and logistic regression analysis. Results The subjects' mean age was 39.58 ± 6.69 years, of whom, 47% were widowed; they were mostly housewives with a mean schooling of 7.97 ± 4.31 years, and 74.2% had insufficient income. Prior to the intervention, women who were the head of the household and had poor level of health-promoting behaviors were selected. There was no significant difference between the two groups in mean score of the components of the health-promoting model (P < 0.05). The intervention group had significantly better performance in physical health-promoting behaviors, two months after the intervention (P < 0.001). Conclusions The supportive-educational intervention was effective on the physical health-promoting behaviors of women who were the head of the household. Thus, this model can be used as a framework for planning interventions to promote the physical health of such women.